Healthcare and human dignity : law matters - McClellan, Frank M. (Critical issues in health and medicine., 2020)
The individual and structural biases that affect the American healthcare system have serious emotional and physical consequences that all too often go unseen. These biases are often rooted in power, class, racial, gender or sexual orientation prejudices, and as a result, the injured parties usually lack the resources needed to protect themselves. In Healthcare and Human Dignity, individual worth, equality, and autonomy emerge as the dominant values at stake in encounters with doctors, nurses, hospitals, and drug companies. Although the public is aware of legal battles over autonomy and dignity in the context of death, the everyday patient's need for dignity has received scant attention. Thus, in Healthcare, law professor Frank McClellan's collection of cases and individual experiences bring these stories to life and establish beyond doubt that human dignity is of utmost priority in the everyday process of healthcare decision making.